2019
DOI: 10.1093/jtm/taz064
|View full text |Cite
|
Sign up to set email alerts
|

‘More than devastating’—patient experiences and neurological sequelae of Japanese encephalitis§

Abstract: Background Japanese encephalitis (JE), caused by the mosquito-borne JE virus, is a vaccine-preventable disease endemic to much of Asia. Travellers from non-endemic areas are susceptible if they travel to a JE endemic area. Although the risk to travellers of JE is low, the consequences may be severe. Methods Here, we describe three cases of JE in British travellers occurring in 2014–15. In addition, we report, through intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…21 It also has high morbidity with 44% of survivors experiencing long-term neurological sequelae including quadriplegia, ventilator dependence, and locked-in syndrome. [21][22][23] JEV is transmitted between birds and swine in enzootic cycles via mosquito vectors, mainly Culex spp. (Fig.…”
Section: Clinical Features and Epidemiologymentioning
confidence: 99%
“…21 It also has high morbidity with 44% of survivors experiencing long-term neurological sequelae including quadriplegia, ventilator dependence, and locked-in syndrome. [21][22][23] JEV is transmitted between birds and swine in enzootic cycles via mosquito vectors, mainly Culex spp. (Fig.…”
Section: Clinical Features and Epidemiologymentioning
confidence: 99%
“…23 Other viral infections such as dengue, chikungunya and Japanese encephalitis also caused prolonged symptoms. [24][25][26] Earlier studies found the five most common prolonged COVID-19 symptoms were fatigue, headache, attention difficulty, loss of hair, and difficulty in breathing, among 50 identified long-term problems of COVID-19. Other studies reported fatigue and dyspnoea were among the most occurred symptoms post-COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most human JEV infections are asymptomatic or present with flu-like symptoms but can become life-threatening. Severe symptoms include seizures, flaccid paralysis, leukopenia, cardiac arrests, paraplegia, cerebral oedema and respiratory depression which can result in lifelong neurological sequelae [2, 3]. Clinical cases of JE show a case fatality rate of 5–40 % (and 30–50 % of survivors may have prolonged severe neurological manifestations [4–6]).…”
Section: Presentationmentioning
confidence: 99%